A competitive mechanism selecting verb-second versus verb-final word order in causative and argumentative clauses of spoken Dutch: A corpus-linguistic study. (September 2018) - Kempen, Gerard; Harbusch, Karin
Abstract: In Dutch and German, the canonical order of subject, object(s) and finite verb is 'verb-second' (V2) in main but 'verb-final' (VF) in subordinate clauses. This occasionally leads to the production of noncanonical word orders. Familiar examples are causative and argumentative clauses introduced by a subordinating conjunction (Du. omdat, Ger. weil 'because'): the omdat/weil -V2 phenomenon. Such clauses may also be introduced by coordinating conjunctions (Du. want, Ger. denn ), which license V2 exclusively. However, want/denn -VF structures are unknown. We present the results of a corpus study on the incidence of omdat -V2 in spoken Dutch, and compare them to published data on weil -V2 in spoken German. Basic findings: omdat -V2 is much less frequent than weil -V2 (ratio almost 1:8); and the frequency relations between coordinating and subordinating conjunctions are opposite ( want >> omdat ; denn << weil ). We propose that conjunction selection and V2/VF selection proceed partly independently, and sometimes miscommunicate—e.g. yielding omdat/weil paired with V2. Want/denn -VF pairs do not occur because want/denn clauses are planned as autonomous sentences, which take V2 by default. We sketch a simple feedforward neural network with two layers of nodes (representing conjunctions and word orders, respectively) that can simulate the observed data pattern through inhibition-based competition of the alternative choices within the node layers. Highlights: Corpus study into noncanonical verb-second order in Dutch explanatory clauses: The conjunction omdat 'because' only licenses verb-final word order (canonical). Such noncanonical orders occur much less frequently than in German pendants. Our uniform account of this contrast uses inhibition-based competition processes. Whose outcomes vary due to cross-linguistic lexico-syntactic frequency contrasts.